Influencia de la formación extracurricular en el rendimiento académico de Inglés de 1° año de Idiomas, UNT, Trujillo, 2018 - Arias Escajadillo, María Sarita (2019)
The present research titled: Influence of an extracurricular course in the English performance of English of Languages first year students at the National University of Trujillo in 2018 had as main objective to determine the influence of the extracurricular course in the academic performance of English of the first year students at UNT 2018. Likewise, it emphasizes the need to have an English workshop to reinforce student learning and / or take a course in parallel with the classes taught at the University to improve their performance in English. A quasi-experimental design was applied in which 35 students from the National University of Trujillo participated, who were divided into two groups: a control group consisting of 18 students and an experimental group consisting of 17 students. A pre-test and a post-test in both groups were considered asinstrumentsto determine their academic performance and Student´s “T” statistic test was also applied to determine if there was a significant relationship between the development of an extracurricular course and academic performance of the students; which was evidenced in the results obtained. However, we believe that it would be important to design a workshop with a longer duration and continue researching on the subject.